Characterization and phylogenetic relationship of the complete chloroplast genome of a Chinese traditional medicinal plant Potentilla anserina L. Issue 9 (2nd September 2022) - Tang, Chuyu; Li, Xiuzhang; Chen, Jianbo; Liang, Jing; Wang, Tao; Li, Yuling
Abstract: Potentilla anserina L. is an important traditional Chinese medicinal herb and edible plant with a long usage history. As an indispensable sustainable resource, it has various pharmacological functions and active ingredients. Here, we report its complete chloroplast (cp) genome for the first time. The complete chloroplast genome of Potentilla anserina L. (OL678458) was 155, 659 bp in length and contained a pair of inverted repeat regions (IRa and IRb, 25, 947 bp), a large single-copy region (LSC, 85, 052 bp), and a small single-copy region (SSC, 18, 713 bp). A total of 118 functional genes were observed in this cp genome, including 80 protein-coding genes, 30 transfer RNA genes, and eight ribosomal RNA genes. Phylogenetic analysis indicated that P. anserina has the closest relationship with Potentilla lineata .